(untitled) (Proceedings of International Educators Conference, 2023)
Observation of English modern detective genre and peculiarities of Uzbek detective genre is the main topic of this article. Comparative analysis of the Uzbek and English detective genres have been studied in the works of D. Buranov and other historical works. Some similarities and differences between Uzbek and English detective genres have been shown in this paper.